Kitchenspace : women, fiestas, and everyday life in central Mexico - Christie, Maria Elisa (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2008)
A pioneering ethnography of a crucial, yet often undervalued, site of family and community building--the kitchen.